Interface Engineering of a 2D/2D BiVO4/Bi4V2O10 Heterostructure with Improved Photocatalytic Photoredox Activity - Zhu, Kai (Langmuir : the ACS journal of surfaces and colloids, 2022)
Bismuth vanadate (BiVO4) is a promising photocatalyst for water pollution degradation and photocatalytic oxygen evolution. In this work, we prepared 2D/2D BiVO4-Bi4V2O10 heterostructure with tight interfacial contact via a facile one-step hydrothermal process. The crystal structure and morphology of the samples could be easily regulated by changing the pH values of the solution. The BiVO4-Bi4V2O10 heterostructure exhibited an enhanced photodegradation rate of Cr(VI) and oxygen evolution that of bare BiVO4, indicating that the synergistic effect and the interfacial fusions between BiVO4 and Bi4V2O10 can effectively promote the migration and separation rate of photoexcited charge carriers